Morphometric study of two snowtrouts Schizothorax curvifrons and Schizothorax niger of Dal Lake, Kashmir: Morphometry of snowtrouts - Bala, Inab M.; Shah, Tasaduq H.; Bhat, Farooz. A.; Abubakr, Adnan; Chesti, Anayitullah; Nazir, Nageena; Mushtaq, Syed Talia; Rashid, Ifrah; Mushtaq, Shafiya (Journal of the Inland Fisheries Society of India, 2023)
Schizothoracids or snow trouts are indigenous fishes of Kashmir and serve as important food sources for the local population. Fishes belonging to the genus Schizothorax are highly sensitive to environmental changes and may also be used as bio-indicators of aquatic pollution. The study was conducted at Dal Lake, Kashmir to analyze thirteen morphometric measurements of Schizothorax curvifrons and Schizothorax niger. The total length of S. curvifrons and S. niger ranged from 86.62 to 131.66 mm and 82.4 to 235.95 mm, respectively. A positive relationship was found between various morphometric characters with coefficient of determination (R2) values ranging from 0.43-0.94 and 0.87-0.98 for S. curvifrons and S. niger, respectively. The highest R2 values were obtained for total length and standard length for both species while the lowest values were obtained for total length and pre-pectoral length (R2=0.43) in the case of S. curvifrons and total length and dorsal fin length (R2 =0.87) in case of S. niger.